Peran Mahasiswa KKN Tematik UIN Datokarama terhadap Generasi Muda dalam Melestarikan Kebudayaan di Desa Towale melalui “Festival Towale” - Reaki Muliyana; Fauzan Afif; Dinda Dinda; Dewi Pratiwi; Khairunnisa Akmal; Mutiara Mutiara; Delia Rizka Sri Ramadhani; Sunardi Sunardi (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
The UIN Datokarama Thematic Community Service program has successfully organized the Towale Festival as an effort to revitalize the local culture of Towale Village. This study aims to analyze the impact of the festival on increasing young people's awareness of the importance of cultural preservation and the festival's contribution to strengthening the cultural identity of Towale Village. Through a qualitative method involving participatory observation and in-depth interviews, this study found that the Towale Festival has successfully created a space for young people to interact with their cultural heritage. In addition, the festival has also encouraged the emergence of new initiatives in cultural preservation at the community level. The results of this study indicate that activities such as the Towale Festival have great potential to strengthen local cultural values and involve young people in the preservation process.